An Evaluation of Holistic Integrative Early Childhood Education in Indonesia - Damaiyanti, Heny; Harapan, Edi; Puspita, Yenny (Journal of Social Work and Science Education, 2020)
This study evaluated the integrative holistic early childhood education at Ananda Palembang Kindergarten. The evaluation model used in this study is the CIPP Model. The data analysis technique used was qualitative approach. Data were collected through interviews, observation and documentation study. The results showed that 1) context evaluation states that there is no strong legal foundation in the integrative holistic early childhood development program in Ananda Palembang Kindergarten; 2) input evaluation states that Ananda Palembang Kindergarten has been running existing services in holistic integrative early childhood education by having adequate resources; 3) process evaluation states that Ananda Palembang Kindergarten in education, health and nutrition, nursing, care services, protection services and welfare services has been implemented in this institution; 4) product evaluation states that Ananda Kindergarten has been proven by being accredited A in 2018. This paper contributes to other Kindergarten in Indonesia where they will have good accreditation could see Ananda Palembang Kindergarten.